Implementing assuring forward per hop behaviour class in web servers with dynamic scheduling and selective discards. (29th June 2009) - Semprebom, Tiago; De Oliveira, Romulo Silva; Montez, Carlos
This paper proposes an approach for services differentiation in web servers that preserves the network end-to-end quality of service (QoS) mapping in conformance to per hop behaviour assuring forward group. This novel approach uses dynamic scheduling techniques and selective discard of requests to provide a proportional service differentiation to web clients. A prototype was built over the Apache web server and measurements were carried out aiming to evaluate the approach, contrasting it with other traditional techniques of services differentiation.